The demand for safe liquid assets and the implications of issuing a Central Bank Digital Currency for bank funding instruments - Müller, Carola (Norges Bank, 2020)
The pros and cons of issuing a Central Bank Digital Currency (CBDC) is currently debated by Norges Bank and other central banks. A CBDC would grant access to the central bank balance sheet to a broader set of economic agents, including for example companies or individuals. How such access would be designed or administered are topics of the discussion. One dimension to consider is the potential impact on the stability of the financial system through the effect of CBDC issuance on bank funding markets. This article provides an overview on research related to the demand for financial institutions' funding instruments and derives implications for the issuance of a CBDC. A key message is that CBDC has the potential to substantially crowd out bank funding instruments due to its superior safety features.
11250/2690368
Keywords: Graue Literatur; Central bank digital currencies; safe assets; bank funding markets; financial stability; money demand